2017
DOI: 10.1021/acs.jafc.7b00026
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic Diarylheptanoid Asadanin as the Main Contributor to the Bitter Off-Taste in Hazelnuts (Corylus avellana L.)

Abstract: Activity-guided fractionation and taste dilution analysis (TDA), followed by LC-MS/MS, LC-TOF-MS, and 1D/2D-NMR spectroscopy, led to the identification of the cyclic diarylheptanoid asadanin exhibiting a human bitter recognition threshold of 13 μmol/kg, as the major inducer of the sporadic bitter off-taste of hazelnut kernels (Corylus avellana L.). Sensory analysis of hazelnut samples from two origins (Ordu/2013 and Akçakoca/2014) and from Cimiciato-infected hazelnut kernels, followed by LC-MS/MS quantitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Organoleptic characteristics are attributed to the presence of diarylheptanoids. Singldinger et al (2017) identified asadanin, a cyclic diarylhepatanoids responsible for the bitter off-taste in Corylus avellana.…”
Section: Introductionmentioning
confidence: 99%
“…Organoleptic characteristics are attributed to the presence of diarylheptanoids. Singldinger et al (2017) identified asadanin, a cyclic diarylhepatanoids responsible for the bitter off-taste in Corylus avellana.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted diarylheptanoids can be fractionated using open column chromatography (CC), vacuum liquid chromatography (VLC) [34,60,61], middle pressure liquid chromatography (MPLC) [62,63], flash chromatography [64,65], preparative thin-layer chromatography (TLC) [66], or preparative high-performance liquid chromatography (HPLC) ( Table 2) [67]. Cyclic MPLC has also been employed [47].…”
Section: Isolationmentioning
confidence: 99%
“…The mass analyzers used in the characterization of diarylheptanoids are time-of-flight (TOF) MS, which enables accurate mass analysis [50,53,63,136], triple-quadrupole (QQQ) MS [75,146,174] that provides additional structural information by the observation of the fragmentation pattern of the target analytes, while quadrupole-time-of-flight (Q-TOF) technique offers exact mass measurement of both precursor and fragment ions [49,175,176]. High-resolution ion trap MS analyzer was also applied in the characterization of diarylheptanoid fragmentation in Z. officinale [135].…”
Section: Ionization Interfaces Mass Analyzersmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional biphenyl heptanoids, such as deoxoasadanin ( 1b ), epiasadanol ( 1c ), isoasadanol ( 2 ), and di- and trideoxyasadanin-8-ene ( 3 ) were isolated from Ostrya japonica [48]. Recently, Singldinger et al isolated asadanin ( 1a ) from hazelnuts ( Corylus avellana L.) as the main contributor to the bitter off-taste and reported complete analysis and assignment of all the proton and carbon resonances of the molecule [49].…”
Section: Isolation Structural Features and Biological Propertiesmentioning
confidence: 99%